Full-fat soybeans for growing-finishing swine - Lafferty, D.T.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs fed full-fat, processed soybeans (FFPS) in place of soybean meal (SBM, 44% CP) gained adequately and produced carcasses with lean measurements equal to those of pigs fed soybean meal. Backfat and belly fat were considerably softer on carcasses of pigs fed FFPS, and total fat content of loin eye muscle was greater in FFPS carcasses than in carcasses of pigs fed SBM. Taste panel observations showed no differences in flavor, juiciness, tenderness or over-all acceptability of pork chops produced by either diet. Barrows gained faster than gilts regardless of treatment and barrows had firmer carcasses. Gilt carcasses had a larger percentage of lean cuts, more loin eye area, more length, less backfat, and higher ham-loin indexes than barrow carcasses regardless of treatment.
Swine Industry Day 1971 is known as Swine Day, 1971
Keywords: Swine; full-fat, processed soybeans (FFPS); Growing-finishing pigs; Carcasses